Direct and indirect genetic effects of a social supergene. Issue 5 (4th January 2023) - Arsenault, Samuel V.; Riba‐Grognuz, Oksana; Shoemaker, DeWayne; Hunt, Brendan G.; Keller, Laurent
Abstract: Indirect genetic effects describe phenotypic variation that results from differences in the genotypic composition of social partners. Such effects represent heritable sources of environmental variation in eusocial organisms because individuals are typically reared by their siblings. In the fire ant Solenopsis invicta, a social supergene exhibits striking indirect genetic effects on worker regulation of colony queen number, such that the genotypic composition of workers at the supergene determines whether colonies contain a single or multiple queens. We assessed the direct and indirect genetic effects of this supergene on gene expression in brains and abdominal tissues from laboratory‐reared workers and compared these with previously published data from field‐collected prereproductive queens. We found that direct genetic effects caused larger gene expression changes and were more consistent across tissue types and castes than indirect genetic effects. Indirect genetic effects influenced the expression of many loci but were generally restricted to the abdominal tissues. Further, indirect genetic effects were only detected when the genotypic composition of social partners differed throughout the development and adult life of focal workers, and were often only significant with relatively lenient statistical cutoffs. Our study provides insight into direct and indirect genetic effects of a social supergene on gene regulatory dynamics across tissues and castes in a complex society.